Causal Analysis and Prevention Strategies for Safety Risks in Prefabricated Building Construction Based on Accident Data and Complex Network Theory - Wei Liu; Xiao Luo; Baojun Liang; Junhao Xie (Buildings)
As China’s construction industry pays increasing attention to occupational health, prefabricated buildings, as an important direction for industry transformation, are gradually gaining widespread attention. However, because relevant management regulations have not yet been perfected, work-related injuries still occur from time to time. In order to comprehensively analyze safety risks in prefabricated building construction (PBC), this article systematically discusses construction safety risks and their causal relationships based on accident data and complex network theory. By constructing a network model of safety accident causes in PBC, the topology of the network was evaluated, the relationship between accidents and safety risks was revealed, and key safety risk factors were identified. Research shows that the attack strategies of betweenness centrality and degree centrality can significantly affect the stability of the network structure, and the EffG attack strategy performs better in identifying key nodes. In addition, human factors and management factors are the main causes of accidents. In particular, the two factors of insufficient safety education and training and insufficient safety hazard investigation play a decisive role in network connectivity. This study also further analyzed the formation probabilities of critical risk paths for various types of accidents. Among them, object impact accidents have the highest probability of occurrence, reaching 0.19779, while collapse accidents have the lowest probability of occurrence at only 0.02046. In response to these findings, this article proposes strategies, such as strengthening safety training, regular hidden danger inspections, and optimizing on-site management, to reduce construction safety risks and promote the sustainable development of the construction industry.